2020
DOI: 10.3390/pharmaceutics12090895
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intraparenchymal Infusion Distributions: Modeling and Analyses of Human Glioblastoma Trials

Abstract: Intra-parenchymal injection and delivery of therapeutic agents have been used in clinical trials for brain cancer and other neurodegenerative diseases. The complexity of transport pathways in tissue makes it difficult to envision therapeutic agent distribution from clinical MR images. Computer-assisted planning has been proposed to mitigate risk for inadequate delivery through quantitative understanding of infusion characteristics. We present results from human studies and simulations of intratumoral infusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…Although one solution may be direct intracranial delivery of agents, this highly invasive approach will not be suitable for all patients and faces significant challenges in achieving equal and persistent drug distribution throughout the tumor (33,45,46). Another potential approach may be the use of ex vivo activated autologous T cells combined with T cell engaging therapies.…”
Section: Immune Checkpoint Blockade and T Cell Directed Immunotherapymentioning
confidence: 99%
“…Although one solution may be direct intracranial delivery of agents, this highly invasive approach will not be suitable for all patients and faces significant challenges in achieving equal and persistent drug distribution throughout the tumor (33,45,46). Another potential approach may be the use of ex vivo activated autologous T cells combined with T cell engaging therapies.…”
Section: Immune Checkpoint Blockade and T Cell Directed Immunotherapymentioning
confidence: 99%
“…Fluorouracil, carmustine, cisplatin, and doxorubicin could be delivered in large volumes when administered into relatively isotropic tissue, while paclitaxel and methotrexate were able to cover enlarged regions upon delivery into anisotropic tissues [ 62 ]. Similarly, Brady et al modelled parenchymal fluid mechanics using simulations of intra-tumoral infusions in GBM patients, measuring distributions of traced compounds with MRI and positron emission topography (PET) [ 63 ]. From this, they confirmed that convection dominates over effects of diffusion in the context of biological agents or protein-sized molecules delivered by CED despite very small fluid speeds.…”
Section: Limitations and Recent Developments In The Preclinical Settingmentioning
confidence: 99%
“…Specifically, expansion of WM was found to significantly raise its hydraulic conductivity, making the tissue less anisotropic. This suggests that shunting of infusions in WM tracts is not primarily due to anisotropy of the neuronal fibers, but rather due to their expandability that permits conductivity to increase dramatically [ 63 ].…”
Section: Limitations and Recent Developments In The Preclinical Settingmentioning
confidence: 99%
“…Fluorouracil, carmustine, cisplatin, and doxorubicin could be delivered in large volumes when administered into relatively isotropic tissue, while paclitaxel and methotrexate were able to cover enlarged regions upon delivery into anisotropic tissues 57 . Similarly, Brady et al modelled parenchymal fluid mechanics using simulations of intra-tumoral infusions in GBM patients, measuring distributions of traced compounds with MRI and positron emission topography (PET) 58 . From this, they confirmed that convection dominates over effects of diffusion in the context of biological agents or protein-sized molecules delivered by CED despite very small fluid speeds.…”
Section: Drug Distributionmentioning
confidence: 99%
“…Specifically, expansion of WM was found to significantly raise its hydraulic conductivity, making the tissue less anisotropic. This suggests that shunting of infusions in WM tracts is not primarily due to anisotropy of the neuronal fibers, but rather due to their expandability that permits conductivity to increase dramatically 58 .…”
Section: Drug Distributionmentioning
confidence: 99%